Radiant heat transfer of bicycle helmets and visors - Brühwiler, P. (Journal of Sports Sciences, 2008)
Twenty-six bicycle helmets and their associated visors were characterized for radiant heat transfer using a thermal manikin headform in a climate chamber to assess their ability to protect the wearer from heating by the sun. A single configuration for applied radiant flow of 9.3 W was used to assess the roles of the forward and upper vents and the visor. The helmets shielded 50-75% of the radiant heating without a visor and 65-85% with one. Twenty-three visors were shown to result in a relevant reduction of radiant heating of the face (>0.5 W), with 15 reaching approximately 1 W. Heating of the visor and/or helmet and subsequent heating of the air flowing into the helmet was nevertheless found to be a relevant effect in many cases, suggesting that simple measures like reflective upper surfaces could noticeably improve the radiant heat rejection without changing the helmet structure. The forward vents in the helmets that allow the transmission of radiant heat are often important for forced convection, so that minimizing radiant heating geneally reduces the maximization of forced convective heat loss for current helmets.